COVID Induced Reverse Migration in Uttarakhand, India: Issues and Opportunities - Sweta Pant; Arvind Singh Yadav (Archives of Current Research International, 2025)
One of the most dangerous and pressing issues humanity has encountered recently is the COVID-19 pandemic, which has had a negative economic, social, and psychological impact on the people of India and the entire world. Many people have lost their lives because of the pandemic, and many more are currently suffering from its aftereffects. Because of the lockdown and lack of resources, the pandemic has also presented significant challenges to policymakers in India and around the world, particularly in rural areas. During the pandemic reverse migration from the urban to rural areas started all around the world. The Himalayan state of Uttarakhand witnessed a great reverse migration to the villages during the pandemic. This research paper investigates the main reasons behind the reverse migration during COVID, with problems faced by reverse migrants in their native villages and towns that forced them to migrate back. The study was conducted with the help of questionnaires and interviews of 40 respondents. The main reasons behind the reverse migration were the government-implemented lockdown, huge job losses, poor food and health supplies, problems of housing, fear of COVID infections, the sudden homesickness generated due to COVID, etc. There were also challenges to the government institutions, NGOs, and social groups of the state to facilitate efficient health services, places for residence, and food and create livelihood opportunities in the villages which have experienced huge reverse migration. But all these, mainly the lack of job opportunities and health and educational facilities in rural areas, proved to be insufficient, so migrants were compelled to go back to their working places just after the removal of lockdown by the govt. The study concludes that the reverse migration in Uttarakhand was loaded with several issues and opportunities which are important to investigate; the study can further generate insight for researchers and policymakers. Employment generation in the agriculture, horticulture, and tourism sectors with the development of education, health, and infrastructural facilities and judicious use of available land, water, and forest resources would prove helpful to reverse migrants to get employment at their native places, and it will also reduce the pace of migration in the hill state.